Operative Versus Nonoperative Treatment of Acute Displaced Distal Clavicle Fractures: A Multicenter Randomized Controlled Trial. Issue 12 (December 2021) - Hall, Jeremy A.; Schemitsch, Christine E.; Vicente, Milena R.; Dehghan, Niloofar; Nauth, Aaron; Nowak, Lauren L.; Schemitsch, Emil H.; McKee, Michael D.
Abstract : Objectives: To evaluate the differences in patient outcomes after operative or nonoperative treatment of displaced, type II distal clavicle fractures. Design: Multicenter, prospective, randomized controlled trial. Setting: Level I trauma centers. Patients/Participants: Patients with completely displaced type II distal clavicle fractures were included. Fifty-seven patients were randomized: 27 to the operative group and 30 to the nonoperative group. Intervention: Patients randomized to nonoperative care received a standard shoulder sling, followed by pendulum or gentle range of motion shoulder exercises at any time as directed by the attending surgeon. Patients randomized to the operative group received plate fixation with a precontoured distal clavicular plate or a "hook" plate within 28 days from injury. Main Outcome Measure: Disabilities of the Arm, Shoulder and Hand scores at 1 year. Results: There were no between-group differences in Disabilities of the Arm, Shoulder and Hand or Constant scores at 1 year. More patients in the operative group went on to union (95% vs. 64%, P = 0.02) within 1 year. Twelve patients in the operative group underwent a second operation for implant removal (12/27, 44%). In the nonoperative group, 6 patients (6/30, 20%) subsequently underwent 8 operative procedures. Conclusion: Although this study failed to demonstrate a difference in functional outcomes between operative and nonoperative treatment of Neer type II distal clavicle fractures, nonoperative management led to more complications including a moderate rate of nonunion, which often required secondary surgery to correct, a higher rate of early dissatisfaction with shoulder appearance, and a delayed return to activities in the first 6 months. Operative management provided a safe and reliable treatment option with few complications, but often required secondary implant removal, especially with hook plate fixation. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.